THE APPLICATION OF E-MODULES TO IMPROVE THE LEARNING OUTCOMES OF PHASE F ON STUDENTS' KNOWLEDGE OF THE FUNCTION OF MILLING MACHINE PARTS - Ah. Noval Faqih Alhakim; Muhammad Khumaedi (SOSIOEDUKASI, 2026)
The low understanding of students in the competence of Machining Engineering expertise on the function of fresh machine parts is often caused by the learning process that is still dominated by conventional methods and the use of print modules that are less interactive. This study aims to analyze the feasibility level of e-modules, test the improvement of students' Phase F knowledge learning outcomes, and analyze the effectiveness of the application of e-modules compared to conventional lecture methods and print modules. This study is a quasi experiment with a nonequivalent control group design. The subjects of this study are students of class XI of Mechanical Engineering at SMK Negeri 1 Semarang, which are divided into experimental groups and control groups. The data collection instrument used an expert validation questionnaire for e-module feasibility and test instruments (pre-test and post-test) to measure cognitive achievement. Based on the results of the expert assessment analysis, the e-module was declared valid with a CVR value of ≥ 0.75 and a CVI of ≥ 0.78, and was considered reliable with a percentage of agreement of 90%. The effectiveness test through N-Gain proved that experimental classes using e-modules experienced an increase in learning outcomes of 78.63% (high category) with an average post-test score of 70.00. In conclusion, the application of e-modules for the function of fresh machine parts is very feasible and has proven to be significantly more effective in improving students' knowledge learning outcomes compared to conventional learning media.